Nutcracker syndrome due to aorto-mesenteric compression in adults: Case report and literature review - Elhattabi, Khalid (Int J Surg Case Rep, 2020)
Nutcracker syndrome is a rare entity that corresponds to an abdominal pain following compression of the left renal vein during its passage between the aorta and the superior mesenteric artery, with a peak prevalence in adults between 20 and 30 years old, The typical clinical presentation includes hematuria, orthostatic proteinuria with or without flank pain. doppler ultrasound has a sensitivity of 78% and specificity of 100%, Both CT and MRI can show the compression of the left renal vein between the aorta and the superior mesenteric artery. We report the case of a young patient admitted to the emergency room for abdominal pain mainly localized in the left hypochondrium, with microscopic hematuria, a CT scan was performed showing a reduced aorto mesenteric angle with a compression of the left renal vein and collateralization of venous circulation of left gonadal vein.